Health Smart Home Services incorporating a MAR-based Energy Consumption Awareness System - Kim, M.; Lee, J.; Wang, Xiangyu; Kim, J. (Kluwer Academic Publishers, 2014)
Health smart homes would enable people suffering from various diseases and handicaps to live an autonomous lifestyle in their own residences. The concept of the health smart home emphasizes ‘aging in place’, where residents enjoy a healthy independent life in their own homes as they become older. While energy saving is one of the crucial issues to be addressed in domestic buildings, there is little research into household energy consumption in health smart homes. This paper identifies each variable’s implications for health smart home services and highlights its application to energy consumption awareness. We also introduce Mobile Augmented Reality (MAR) to simulate energy consumption awareness in health smart homes. Firstly, the research proposes a framework for constructing health smart home services with a focus on the practicability of each variable from the perspective of supporting user experience in home settings. Rather than address each variable in isolation, we consider comprehensive issues in terms of service effectiveness in supporting a healthy life at home. Additionally, the innovative MAR application associated with energy use is presented as a new solution for household energy consumption awareness. The proposed application will be a basis for the perspectives of future research directions on health smart home services.